Teatralność procesu sądowego : kilka uwag o profesjonalizmie - Kaczmarek, Przemysław
The aim of the paper is to answer the question: what image of aprofessional role does the vision of acourt trial as atheatre contain? In carrying out such atask, first of all, Iwill present the reasons that justify comparing the theatrical practice to acourt hearing. When carrying out this procedure, Iwill pay attention to the concept of role, the ritualization of activities, the architecture of space, and functions of the role performers’ clothing. From these findings, adramatical vision of acourt trial emerges, modelled on atheatrical performance. It assumes that the performing of arole by the actor and the judge or thelawyer is largely defined by factors external to the interpreter. Such an approach to the exercise of the profession can be related to the dramatic vision of the role in Erving Goffman’s theatrical metaphor. In this perspective, it is assumed that exercising arole is aperformance that can lead to two images of the professional ethos.They are characterized by an attitude of identification with the role and an instrumental distance to the profession. Iintend to question both of these views.By carrying out this task, Iwill show that presenting acourt trial as atheater does not have to assume the image of ajudge,alawyer whose task is to develop the ability to adapt to the rules of the profession and faithfully reproduce them in the cases under consideration. In presenting this position, Iuse the findings of theatrologist Jerzy Grotowski and the anthropological research of Victor Turner, focusing on the idea of liminality.
Keywords: court trial; theatre; lawyer; judge; professionalism; institutional morality; totality